Influence of gamma radiation on the photoluminescent properties of CdZnTe/ZnTe QW - M. Sharibaev; A. Shamuratova; Saparniyazova G. (Genius Journals, 2025)
The effect of electron and X-ray irradiation on the optical characteristics of CdZnTe/ZnTe quantum-size structures has been investigated. A comparison between the results of both irradiations has shown an essential role of electron excitation in radiation enhancement of Cd diffusion that is one of the reasons for degradation of the II−VI-based quantum-size structures.
Keywords: Irradiation; quantum wells; photoluminescence